Mandeville's Travails : Merging Travel, Theory, and Commentary. - Tobienne, Francis, Jr.; Tobienne, Francis (Blue Ridge Summit : University of Delaware Press, 2016)
Mandeville's Travails challenges the less than serious stereotyping of travel as both genre and theoretical framework. Instead, and by examining the position of travel, a deeper sense of the human species can be appreciated beyond the displaced borders of language, ritual, and culture.
Intro -- Contents -- Acknowledgments -- Introduction -- Chapter One: Travel as Ideological Belief -- Chapter Two: Problems, Observations, and Memory -- Chapter Three: Regularities and Hypothesis -- Chapter Four: Recorded Experiment and Reproducibility -- Chapter Five: (A) Heuristic -- Abbreviations -- Bibliography -- Index -- About the Author.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Voyages and travels--Early works to 1800.; Electronic books